Advanced Elastocaloric Cooling Devices Based on Shape Memory Alloy Films - Brüderlin, Florian (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie, 2022)
Elastocaloric cooling is an emerging solid-state cooling technology with the potential to provide environmentally friendly, efficient cooling. The elastocaloric effect in superelastic shape memory alloy films is used to develop advanced cooling devices for small-scale applications. Cascaded and parallelized devices are developed to increase device temperature span and cooling capacity. The concepts are proven experimentally, a maximum temperature span of 27° C is achieved in a cascaded device.